Simulation analysis and experimental study on vibration reduction performance of groove-textured friction pair surfaces - Tang, Wusheng (Strojniški vestnik, 2025)
To further investigate the influence of surface texture on the vibration characteristics of friction pair surfaces, this study fabricated groove textured on 45 steel surfaces using laser marking technology, forming a friction pair with chloroprene rubber. Numerical analysis of their friction processes under varying speeds was conducted via the finite element analysis software ABAQUS/Explicit (explicit dynamic solver).The results indicate that with increasing speed, the grooved-texture surface enhances its capability to reduce both the intensity and the continuity of contact stress concentration on the friction plate surface, while simultaneously accelerating the diffusion speed of contact stress from the leading edge to the trailing edge of the friction block, thereby better suppressing its concentration at the leading edge. Meanwhile, friction tests were conducted at varying speeds on the HCM-5 reciprocating friction and wear testing machine for the 45 steel-chloroprene rubber friction pair. The results show that at all speeds, the system damping of the freely decaying oscillation component on the surface of the groove texture after "groove-crossing fluctuations" is significantly increased compared to the non-textured surface. As the speed increases, the damping effect of the groove texture on the vibration of the friction pair surface gradually enhances, and the reduction in energy density at the main frequency of the friction pair surface becomes increasingly evident. This corresponds to the numerical analysis results, illustrating the influence of speed on the improvement of the vibration characteristics of the friction pair surface by the groove texture.
Keywords: friction characteristics; groove textured; hitrost; numerical analysis; numerična analiza,; tekstura z utori; trenje; velocity